(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
The article discusses in detail the role of a healthy lifestyle in human health. Preventing heart disease through a healthy lifestyle is important because science has proven that heart disease is caused by a passive physical life, poor diet and bad habits.